2020
DOI: 10.1186/s12905-020-0884-1
|View full text |Cite
|
Sign up to set email alerts
|

Pattern and correlates of out-of-pocket payment (OOP) on female sterilization in India, 1990–2014

Abstract: Background: Large scale public investment in family welfare programme has made female sterilization a free service in public health centers in India. Besides, it also provides financial compensation to acceptors. Despite these interventions, the use of contraception from private health centers has increased over time, across states and socioeconomic groups in India. Though many studies have examined trends, patterns, and determinants of female sterilization services, studies on out-of-pocket payment (OOP) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 43 publications
1
14
1
Order By: Relevance
“…However, the result also confirmed the high level use of traditional methods among educated women. This result was surprising although there are many other studies support this fact [17,23]. A study also showed that one of the greatest factors supporting traditional contraception use among more educated and wealthier women was not the perceived ineffectiveness of modern methods but their wholesome side effects [33].…”
Section: Plos Onementioning
confidence: 99%
See 3 more Smart Citations
“…However, the result also confirmed the high level use of traditional methods among educated women. This result was surprising although there are many other studies support this fact [17,23]. A study also showed that one of the greatest factors supporting traditional contraception use among more educated and wealthier women was not the perceived ineffectiveness of modern methods but their wholesome side effects [33].…”
Section: Plos Onementioning
confidence: 99%
“…The reason for low prevalence of sterilization and high utilization of temporary methods by Muslim women can be explained by the religious doctrine of Islam which does not favors permanent methods of family planning [29][30][31]. The longstanding heterogeneity of population of India associated with religion and the caste system is still relevant in contraceptive choices [15][16][17]23,32,33].…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations
“…In settings where FPC requires a high out-of-pocket payment, clients with low income may not be able to afford it. Even in countries where FPC services are free, clients may still incur high out-of-pocket expenditure [44]. In developing countries, FPC services are less likely to be available and accessible in rural areas [45].…”
Section: Plos Onementioning
confidence: 99%